O-GlcNAcylation modulates Bmi-1 protein stability and potential oncogenic function in prostate cancer - Li, Y; Wang, L; Liu, J; Zhang, P; An, M; Han, C; Guan, X; Zhang, K (Oncogene, 2017)
The Polycomb group transcriptional repressor Bmi-1 often overexpressed and participated in stem cells self-renewal and tumorigenesis initiating of prostate cancer. In this progression, Bmi-1 protein was regulated by transcription and post-translational modifications (PTMs). Nobly, the underlying PTMs regulation of Bmi-1 is poorly known. Here we use co-immunoprecipitation show that in C4-2 cell line, Bmi-1 directly interacted with OGT which is the only known enzyme catalyzed the O-GlcNAcylation in human. Furthermore, we identified that Ser255 is the site for Bmi-1 O-GlcNAcylation, and O-GlcNAcylation promoted Bmi-1 protein stability and its oncogenic activity. Finally, microarray analysis has characterized potential oncogenes associated pathway subject to repression via the OGT-Bmi-1 axis. Taken together, these results indicate that OGT-mediated O-GlcNAcylation at Ser255 stabilizes Bmi-1 and hence inhibits the TP53, PTEN and CDKN1A/CDKN2A pathway. The study not only uncovers a novel functional PTMs of Bmi-1 but also reveals a unique oncogenic role of O-GlcNAcylation in prostate cancer.